Progress of ursolic acid on the regulation of macrophage: summary and prospect - Feng, Wenjing; Yang, Kehong; Zou, Ying; Xiao, Zhaohua; Qian, Rongkang; Qian, Ronghua (Frontiers in Immunology, 2025)
Ursolic acid (UA), a prevalent pentacyclic triterpenoid found in numerous fruits and herbs, has garnered significant attention for its vital role in anti-inflammatory processes and immune regulation. The study of immune cells has consistently been a focal point, particularly regarding macrophages, which play crucial roles in antigen presentation, immunomodulation, the inflammatory response, and pathogen phagocytosis. This paper reveals the underlying regulatory effects of UA on the function of macrophages and the specific therapeutic effects of UA on a variety of diseases. Owing to the superior effect of UA on macrophages, different types of macrophages in different tissues have been described. Through the multifaceted regulation of macrophage function, UA may provide new ideas for the development of novel anti-inflammatory and immunomodulatory drugs. However, to facilitate its translation into actual medical means, the specific mechanism of UA in macrophages and its clinical application still need to be further studied.